Few Innovative Findings in Plant and Crop Science - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2016)
During last 50 years of research and teaching periods Prof. R.K. Maiti published more than 450 research papers and 42 books (available in R. K. M. Foundation library) in various disciplines of plant and crop science. Out of which he described a brief outline of few innovative research findings. Few hypotheses are put forward and research needs are suggested. (for details contact ratikanta.maiti@gmail.com)...